Challenges in extubating critically ill patients in intensive care units (Research, Society and Development, 2024)
This study aimed to: identify and analyze the main challenges in extubating critically ill patients in intensive care units, with the aim of understanding the factors that influence the success or failure of the procedure. This study consists of an integrative review of the literature. This approach was adopted to theoretically substantiate the topic in question, using articles and books by other authors who previously researched the subject. In the search in the aforementioned databases, the advanced search method was used, using the crossing of Health Sciences Descriptors (DeCS), including the terms: ICU, Critical patient and Intensive care, using the Boolean operator AND. Then, filters were applied to select complete articles available for download and reading in full, published in Portuguese in the last 5 years. The studies address medical, psychosocial and socioeconomic aspects related to patients' quality of life. Analysis of the challenges in extubating critically ill patients in intensive care units revealed significant complexity, which manifests itself in several critical areas of clinical management. The literature points out that early identification of patients suitable for extubation is essential for the success of the procedure, but this decision is often complicated by factors such as comorbidities, hemodynamic instability and muscle weakness acquired in the ICU.